1973
DOI: 10.1021/es60079a002
|View full text |Cite
|
Sign up to set email alerts
|

Ammonium nitrate in airborne particles in Los Angeles

Abstract: After extraction of benzene solubles from airborne particulate matter collected at four Los Angeles sites, a still larger fraction can be extracted with methanol. This contains mostly inorganic materials. Qualitative tests, Kjeldahl titration, 2,4-xylenol nitrate determination, and infrared spectra show it to be principally ammonium nitrate. This salt comprises approximately 10-15% of the total airborne particles in composite samples collected over the year 1971-72.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

1977
1977
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 6 publications
1
16
0
1
Order By: Relevance
“…D 'Ans, 1913), and observations of ammonium, sulphate, and nitrate in PM have appeared in the literature over the past sixty years (cf. Robbins and Cadle, 1958;Fenn et al, 1963;Spurny and Heard, 1969;Heard and Wiffen, 1969;Gordon and Bryan, 1973;Anlauf et al, 1978;Brosset, 1978;Stelson et al, 1979;Tanner, 1983). The partitioning between different phases, including gases, may be predicted using fundamental thermodynamics theory (cf.…”
Section: Introductionmentioning
confidence: 99%
“…D 'Ans, 1913), and observations of ammonium, sulphate, and nitrate in PM have appeared in the literature over the past sixty years (cf. Robbins and Cadle, 1958;Fenn et al, 1963;Spurny and Heard, 1969;Heard and Wiffen, 1969;Gordon and Bryan, 1973;Anlauf et al, 1978;Brosset, 1978;Stelson et al, 1979;Tanner, 1983). The partitioning between different phases, including gases, may be predicted using fundamental thermodynamics theory (cf.…”
Section: Introductionmentioning
confidence: 99%
“…Results show that, Raman Spectra and SEM-EDX structural analysis of the samples can be used very efficiently to identify the pollutants on the ancient walls of historical monuments and thus, some precautions can be taken for restoring such architectures [4,5]. Codes were given to the samples as VA1, VA2.…”
Section: Raman Spectramentioning
confidence: 99%
“…On the other hand, many classes of inorganic and organic compounds and materials can be expected to be major constituents of airborne particulate matter. Different workers have concluded that the principal sulfur and nitrogen species are SO 4 À2 , NO À3 and NH +4 , which are ''urban aerosols'', and suggested that the most likely combinations of these ions are ammonium nitrate [4] and ammonium sulfate [5]. A recent study was done by Raman spectroscopy assisted with XRF and chemical simulation to assess the synergic impacts of guardrails and traffic pollutants on urban soils [6].…”
Section: Introductionmentioning
confidence: 99%
“…Uma parte substancial dos ácidos atmosféricos gerados pela oxidação do SO 2 e NO x é neutralizada pela amônia e os produtos finais são os sais de amônio, na forma de material particulado [36][37][38] . Reações de neutralização parecem ser, juntamente com as deposições seca e úmida, os meios de remoção mais comuns dos compostos ácidos na atmosfera.…”
Section: Importância Ambiental Da Amônia Atmosféricaunclassified